Structure types of names of dishes in Olha Franko’s “Practical cuisine” (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article is concerned with revealing and describing of main structural types of names of dishes in Olha Franko’s cookery book “Practical cuisine”. The term “names of dishes” means first components of culinary recipes, their titles. The author overviews main lines of modern research of gastronomic discourse, in particular linguistic studies. The fact is ascertained there are not enough research papers in Ukrainian linguistics analyzing Ukrainian gastronomic discourse. The general description of cookery books as special editions for using is made. Also these books have historic and social value, reflect changes in material culture of society, in food culture, collective consciousness, style of life of different social class etc. More than 1 000 names of dishes in Olha Franko’s cookery book “Practical cuisine” are analyzed. One-word names are 14 % of all names. They demonstrate typical for Ukrainian language ways of formation of names of dishes and semantic changes: the article contains examples of suffixal derivatives from names of food products, from verbs with meaning of culinary processes, examples of names derived by lexical-semantic method of derivation and by linguistic borrowing.The main types of complex names of dishes are described. The most of them are two-part phrases (more than 68 %). The typical structures are substantive phrases with subordinate words expressed by adjectives, participles, and nouns with prepositions. In most cases subordinate elements regardless of the grammatical form denote necessary ingredients of the dishes and methods of food processing. The dependent components in significantly fewer number of names indicate a qualitative characteristic of the dish (texture, color, taste) or derived from the name of the area where a certain method of cooking is distributed. Names are not massive in details. Methods of further complicating of basic structures and deriving three-, four-, and five-word phrases are described. There is almost complete absence of figurative names and those ones containing prominent assessment among analyzed phrases. The advanced studies are the further analyzing of culinary books published in different periods by using a comparable method. Such essays will reveal changes in gastronomic discourse due to various political, economic, and socio-cultural factors.
Keywords: gastronomic discourse; culinary book; name of dish; complex name; phrase